Fosfato de cálcio bifásico obtido da casca de ovo de galinha reforçada com titânia para bioengenharia tecidual – caracterização fisicoquímica e avaliação do reparo ósseo - Oliveira, Laisa Kindely Ramos de (2023)
The Hydroxyapatite/Anhydrous Dicalcium Phosphate (HA/DCPA - Anhydrous Dicalcium Phosphate) association results in a more soluble and stable bioceramic than HA, but with limited mechanical properties for clinical applications in areas subject to high loads. In order to improve their physical and mechanical properties, motivation dioxide (TiO2) or titania can be incorporated into bioceramics, constituting a promising approach for use in tissue engineering. Objectives: To carry out the physicalmechanical characterization of the HA/DCPA/TiO2 composite and to evaluate the tissue repair process after its implantation in rat calvaria. Methodology: Two bone defects were created in the calvaria of 36 male Wistar rats, divided into three groups: HA/DCPA; HA/DCPA/TiO2 and sham (blood clot). The animals were euthanized at 30, 60 and 90 days and the calvaria remained for histological processing using the hematoxylin/eosin technique. Through histomorphometric analysis, the percentage of newly formed bone, connective tissue, remaining biomaterial and total tissue repair was calculated in relation to the total area of the defect. HA/DCPA/TiO2 was characterized structurally by scanning electron microscopy (SEM), and chemically by energy dispersive x-ray spectroscopy (EDS) and X-ray diffraction (XRD) and tested for apparent density (AD) and porosity tests apparent (PA), water absorption (AA) and compressive strength (CS). The data were examined through statistical analysis using ANOVA for independent samples followed by Tukey's test for intergroup comparison and Student's t test for paired measures for intragroup comparison (p≤0.05). Results: EDS showed oxygen, calcium, phosphorus, and titanium composing the samples. Using SEM the surface of the biomaterials inside the bone defects, the presence of newly formed bone and its interface with the native bone of the calvaria were observed. At the end of the experiment, the HA/DCPA/TiO2 and HA/DCPA groups showed a similar total tissue repair area, but significantly greater than that of the sham group (p<0.001). Physical and mechanical tests showed that HA/DCPA/TiO2 has AD and CR properties within the limits of trabecular bone and with values higher than HA/DCPA.Conclusion: HA/DCPA/TiO2 showed higher rates of densification and compressive strength than HA/DCPA. Biocompatibility and osteoconductivity denote the potential of this bioceramic as a framework for bone engineering.